Bioindicators in radiation protection - Amaral,Ademir (2008)
Biodosimetry is the evaluation of absorbed dose using bioindicators. Among chromosomal aberrations, scoring of dicentrics from peripheral human blood has been used as gold standard for biodosimetry, although in case of large scale incidents its use presents some drawbacks. Advances in technology have led to new investigations allowing or permitting the use of new methods which not only improve this "classical" biodosimetry but permits the design of other bioindicators making possible faster analyses, particularly in events where many persons may have been exposed. This report presents an overview of some recent studies developed by the "Grupo de Estudos em Radioproteção e Radioecologia - GERAR", Nuclear Energy Department of UFPE - Brazil, involving biodosimetry.